2018
DOI: 10.2106/jbjs.17.00955
|View full text |Cite
|
Sign up to set email alerts
|

Free Vascularized Medial Femoral Condyle Bone Graft After Failed Scaphoid Nonunion Surgery

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
1
12
0
4
Order By: Relevance
“…This method has the advantage in that large grafts can easily be obtained and less risk of possible torsion to vascular pedicle. Furthermore, it has elasticity and readily conforms to the small tubular bone [6,10,17]. We found similar results in the union rate and the ROM when compared with other studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This method has the advantage in that large grafts can easily be obtained and less risk of possible torsion to vascular pedicle. Furthermore, it has elasticity and readily conforms to the small tubular bone [6,10,17]. We found similar results in the union rate and the ROM when compared with other studies.…”
Section: Discussionsupporting
confidence: 85%
“…A meta-analysis of Merrell et al [8] demonstrated that VBG showed a significantly better union rate (88%) compared to traditional bone graft (47%). Recent studies have established the efficacy of VBG for the scaphoid nonunion complicated by AVN with a higher union rate and shorter time to union [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these large reviews are mostly based on level 3 evidence / retrospective cohort studies, which limits their utility due to considerable bias. Since this large meta-analysis and systematic review, other studies have demonstrated similar union rates [8,40,41,42,43].…”
Section: Recent Clinical Evidencementioning
confidence: 85%
“…Bei den Rekonstruktionen unter Verwendung eines kortikospongiösen Femurspanes liegen die Heilungsraten zwischen 80 und 100 % [5,[20][21][22][23][24][25]. Selbst in einem selektionierten Krankengut mit ausschließlich voroperierten Patienten heilten immerhin 84 % [26].…”
Section: Degenerative Veränderungenunclassified